2010
DOI: 10.1038/jhh.2010.98
|View full text |Cite
|
Sign up to set email alerts
|

The diverse associations of uric acid with low-grade inflammation, adiponectin and arterial stiffness in never-treated hypertensives

Abstract: The data regarding the role of serum uric acid (SUA) along with subclinical inflammation in the context of hypertensive vascular damage are rather scarce and controversial. Towards this end, we assess the links between SUA, high-sensitivity CRP (hs-CRP), adiponectin and carotid to femoral pulse wave velocity (c-f PWV) in 292 subjects with never-treated stage I-II essential hypertension. On the basis of the median SUA levels (0.31 mmol l À1 ), the study population was divided into subjects with low (n ¼ 149) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 29 publications
2
48
1
3
Order By: Relevance
“…Kanellis et al reported that hyperuricemia might be partially responsible for the inflammatory pathway in vascular smooth muscle cells [34]. However, Tomiyama et al did not detect an independent relationship between the serum uric acid level and baPWV in healthy Japanese subjects [35], Tsioufis et al reported that uric acid was correlated with cfPWV in the early stages of hypertension, but the association between uric acid and PWV disappeared after regression analysis [13], and Lim et al found no association between serum uric acid level and baPWV in healthy Koreans [18]. They explained that uric acid may not affect arterial stiffness in a population at low risk for cardiovascular disease.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Kanellis et al reported that hyperuricemia might be partially responsible for the inflammatory pathway in vascular smooth muscle cells [34]. However, Tomiyama et al did not detect an independent relationship between the serum uric acid level and baPWV in healthy Japanese subjects [35], Tsioufis et al reported that uric acid was correlated with cfPWV in the early stages of hypertension, but the association between uric acid and PWV disappeared after regression analysis [13], and Lim et al found no association between serum uric acid level and baPWV in healthy Koreans [18]. They explained that uric acid may not affect arterial stiffness in a population at low risk for cardiovascular disease.…”
Section: Discussionmentioning
confidence: 94%
“…There are few reports of the relationship between uric acid and PWV [13,18,19], and the results of these studies were inconsistent. Moreover, there is no information on the relationship between uric acid and PWV in postmenopausal women.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…10 These previous studies represented that the relevance of SUA level as a risk factor for arterial stiffness remains controversial. 11 Arterial stiffness can be easily and non-invasively assessed by measuring brachial-ankle pulse wave velocity (ba-PWV), 12,13 which is a suitable screening measure for vascular dysfunction and the development of atherosclerosis in a preventive setting. 14 We previously found that subjects with a high-normal level of cardiovascular risk factors were characterized by a greater incidence of arterial stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that the association of uric acid level with arterial stiffness remains controversial (Chen et al, 2010;Lim et al, 2010;Tsioufis et al, 2011;Fang et al, 2014;Saijo et al, 2005;Bae et al, 2013;Mulè et al, 2014).…”
Section: Measuring Pulse Wave Velocity (Pwv) Is a Noninvasivementioning
confidence: 99%